Pengaruh Penambahan 2,5% Ti-B terhadap Sifat Mekanik Poros Berulir (Screw) Berbahan Dasar 40% Aluminium Bekas dan 60% Piston Bekas - Putri Rachmawati; Andika Wisnujati (Jurnal Engine: Energi, Manufaktur, dan Material, 2017)
Soybean miller machine is an innovative machine that makes it easy for tempeh producers.This machine uses a threaded shaft (screw), making it easier for tempeh producers in producing more higienic tempeh easy and fast threaded shaft (screw) is made of aluminium alloy metal. This research study is intended it find the ideal alloy as material for the manufacture of threaded shaft (screw). This research study used a mixture of 40% aluminium profil and 60% of used pistons with 2.5% Ti-B (Titanium-Baron) as a smooth refiner. The mold used is a metal mold (die casting) with a mold temperature heating of 200oC. The test to know the mechanical properties of the aluminium alloy is tensile and hardness test. Based on the test results of the tes tis that the specimen with heating temperature of 200oC producers a maximum tensile stress of 148.08 MPa, while for vickers hardness testing yields an average hardness of 95.1 Kg/mm2. The results of the experiments using heating temperature of 200oC and 400oC obtained microstructure on aluminium alloy casting specimens with 2.5% Ti-B addition, the most evently formed phase ini all specimens was Aluminium (Al) phase.Universitas Muhammadiyah Yogyakarta